2013
DOI: 10.17711/sm.0185-3325.2013.035
|View full text |Cite
|
Sign up to set email alerts
|

Conocimientos y creencias sobre el trastorno por déficit de atención con hiperactividad en maestros de tres países latinoamericanos

Abstract: SUMMARY BackgroundAttention deficit/hyperactivity disorder (ADHD) is a health problem that affects school functioning. To recognize the teachers´ knowledge and beliefs (KB) about ADHD is important for the development of psychoeducative and training strategies for teachers. There are few Latin American reports about the teachers´ KB and none comparing them among different countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
4
0
4
Order By: Relevance
“…The international guidelines support that a combination of social and pharmacological intervention is the most effective treatment for school-age children with ADHD (National Institute for Health and Care Excellence, 2008). In our review, 9% to 86% of surveyed teachers believed medicine to be an effective treatment for ADHD (Adeosun, Ogun, Fatiregun, & Adeyemo, 2013; Kasten, Coury, & Heron, 1992; PalaciosCruz et al, 2013; Snider, Busch, & Arrowood, 2003) and 8% to 40% knew that stimulants were the most common type of drug used to treat children with ADHD (Akram, Thomson, Boyter, & McLarty, 2009; Alkahtani, 2013; Krowski, 2009; Nur & Kavakci, 2010). Adequate knowledge in these studies was generally low; however, the majority of studies were conducted in non-Western countries, where our review suggests that knowledge about ADHD seems to be underdeveloped in general.…”
Section: Introductionmentioning
confidence: 91%
“…The international guidelines support that a combination of social and pharmacological intervention is the most effective treatment for school-age children with ADHD (National Institute for Health and Care Excellence, 2008). In our review, 9% to 86% of surveyed teachers believed medicine to be an effective treatment for ADHD (Adeosun, Ogun, Fatiregun, & Adeyemo, 2013; Kasten, Coury, & Heron, 1992; PalaciosCruz et al, 2013; Snider, Busch, & Arrowood, 2003) and 8% to 40% knew that stimulants were the most common type of drug used to treat children with ADHD (Akram, Thomson, Boyter, & McLarty, 2009; Alkahtani, 2013; Krowski, 2009; Nur & Kavakci, 2010). Adequate knowledge in these studies was generally low; however, the majority of studies were conducted in non-Western countries, where our review suggests that knowledge about ADHD seems to be underdeveloped in general.…”
Section: Introductionmentioning
confidence: 91%
“…In almost all vulnerable collectives observed, lackings in this area are detected and, often, it is due to a low digital literacy of their parents. In addition, the search of specialized attention for minors with symptoms of behavioural or affective disorder have been associated with a greater intensity of the disorder and a higher educational level of parents (Palacios-Cruz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We can only certify that parents reported their sons and daughters had learning problems. In addition, these studies have demonstrated that only 25% of parents of children and youths with behavioural or affective disorders considered that their children needed medical care and, from them, 13% attended to mental health services (Palacios Cruz et al, 2011).…”
Section: State Of the Artmentioning
confidence: 99%
“…Tan sólo nos consta que sus progenitores afirmaron que sus hijas o hijos tenían problemas de aprendizaje. Además, estos estudios han mostrado que sólo el 25% de los padres de niños y jóvenes con síntomas de trastornos de conducta o del afecto consideraban que sus hijos necesitaban atención médica, y de ellos, el 13% acudió a los servicios de salud mental (Palacios Cruz et al, 2011).…”
Section: Estado De La Cuestiónunclassified
“…En casi todos los colectivos vulnerables observados se detectan carencias en esa área y, en muchas ocasiones, se debe a la baja alfabetización digital de sus progenitores. Además, la búsqueda de atención especializada para los menores con síntomas de trastorno de conducta o de afecto se ha asociado con una mayor intensidad del trastorno y un mayor nivel educativo de los padres (Palacios-Cruz et al, 2011).…”
Section: Conclusionesunclassified